PTU-121 'cholecystectomy' is it best served hot?. (8th June 2018) - Nemeth, Kristof; Quinn, Rob; Kaul, Anil
Abstract : Introduction: The traditional approach to the management of gallstone-related diseases and their acute exacerbations has been conservative for decades. The long standing paradigm of endoscopic extraction of obstructing gallstones with interval cholecystectomy at the end of a cool-down period of 4 to 6 weeks has been challenged in recent years. The National Institute for Health and Care Excellence (NICE, 2014) is recommending that patients with acute cholecystitis should have a laparoscopic cholecystectomy (LC) within a week of admission and the International Association of Pancreatology (IAP, 2013) recommends patients with gallstone pancreatitis to have LC on index admission. Methods: At our hospital we have established a 'hot gallbladder' service in addition to our emergency operating list with once a week dedicated sessions for patients presenting with symptomatic gallstones. A prospective database of all 'hot' patients is maintained and we have carried out a safety and feasibility study of our 2017 cohort of patients. Results: In 2017 409 cases with a median age of 58 year (range: 15 to 97) were referred to our department with hard evidence of gall stone disease. In terms of 'hot gallbladder' cases, 117/409 were deemed suitable for the hot gallbladder list, but 19/117 patients declined surgery. Out of the 98/117 patients 60/98 same admission LCs were performed with good results. The median age of patients was 45 years (range: 20 to 97). The Male: Female Ratio was 1:2.5 54/60 cases were completed laparoscopically, 4/60 required conversion and 1/60 case was abandoned with a cholecystostomy in-situ . The number of subtotal cholecystectomies was 5/60. We had no 30 day mortality and there were no biliary tract injuries. In terms of surgical complications there was 1/60 post-operative haemotoma, 1/60 bile leak and 1/60 intraoperative spillage of gall stones. 3/60 patients required readmission. The length of stay (LOS) for the 'hot gallbladder' cohort was median 6 days (range: 0 to 17). The median length of time between onset of symptoms and presentation to hospital was 1 day (range: 0 to 21 days) and obtaining ultrasound scans took median 1 day (range: 0 to 3). The median waiting time for magnetic resonance cholangiopancreatography (MRCP) was 3 days from admission (range: 1 to 7). In contrast the median LOS for all gall-stone related admissions in the same period were 6 days with range 0 to 56 days. Conclusion: Our experience of managing gallstone disease with prompt cholecystectomy during the same admission shows that this approach provides safe and cost-effective patient care. In order to improve efficiency we are actively working on establishing further 'hot gall bladder' lists during the working week and reduction of waiting times for imaging is desirable.